1995
DOI: 10.1126/science.267.5206.1969
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Electron-Transporting Organic Materials

Abstract: Operating lifetime is the main problem that complicates the use of polymeric light-emitting diodes (LEDs). A class of electron transport (ET) polymers [poly(aryl acrylate) and poly(aryl ether)s] is reported in which moieties with high electron affinities are covalently attached to stable polymer backbones. Devices based on poly(p-phenylenevinylene) (PPV) prepared with these materials exhibited a 30-fold improvement in stability and, in one case, dramatically lower (10 volts versus about 30 volts) operating vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
240
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(252 citation statements)
references
References 26 publications
7
240
0
4
Order By: Relevance
“…Devices prepared with a protective layer structure between the metal and the polymer interface have shown better overall PLED performances. Recently, many research groups 23,24 have reported the use of a triple-layer cathode structure composed of Alq 3 as an electron-transport layer and LiF/Al as electron-injection layers, which significantly increases the device performance of PLEDs. Apart from the metal/polymer interface, a thin hole-injection and -transporting layer of PEDOT:PSS between ITO and the light-emitting layer has also been used in PLED device structures to restrict the formation of charge-trapping sites for charge carriers because of the diffusion of oxygen or indium from ITO into the conjugated polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Devices prepared with a protective layer structure between the metal and the polymer interface have shown better overall PLED performances. Recently, many research groups 23,24 have reported the use of a triple-layer cathode structure composed of Alq 3 as an electron-transport layer and LiF/Al as electron-injection layers, which significantly increases the device performance of PLEDs. Apart from the metal/polymer interface, a thin hole-injection and -transporting layer of PEDOT:PSS between ITO and the light-emitting layer has also been used in PLED device structures to restrict the formation of charge-trapping sites for charge carriers because of the diffusion of oxygen or indium from ITO into the conjugated polymer.…”
Section: Resultsmentioning
confidence: 99%
“…To separate traces of inorganic salts, the polymer was extracted with toluene in a Soxhlet apparatus for 12 h. The resulting solution was evaporated in vacuo to give 94.8 mg (0.182 mmol, yield 89%) of the polymer (3). 1 1 To whom correspondence should be addressed. …”
Section: Polymerizationmentioning
confidence: 99%
“…The limiting factors in determining the operating voltage, luminance efficiency (LE), external quantum efficiency (EQE), and brightness are the degrees of charge injection and transport. Charge injection and transport from both the anode and cathode must be balanced to recombine in the electron-emitting layer to enhance the efficiency and performance of OLED devices [5,6]. Therefore, HITLs play an important role in OLEDs because they allow enhanced hole injection from the indium tin oxide (ITO) anode into the EML, resulting in balanced charge injection/transport and better performance [7].…”
Section: Introductionmentioning
confidence: 99%